2016
DOI: 10.1088/0957-0233/27/8/085005
|View full text |Cite
|
Sign up to set email alerts
|

Procedure to approximately estimate the uncertainty of material ratio parameters due to inhomogeneity of surface roughness

Abstract: Abstract. Roughness parameters that characterize contacting surfaces with regard to friction and wear are commonly stated without uncertainties, or with an uncertainty only taking into account a very limited amount of aspects such as repeatability of reproducibility (homogeneity) of the specimen. This makes it difficult to discriminate between different values of single roughness parameters.Therefore uncertainty assessment methods are required that take all relevant aspects into account. In the literature this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The contributions due to the instrument and its environment are small compared to the characteristics of the object. Previous investigations have already shown how the sensitivity of roughness parameters to the heterogeneity of textures can be determined [27]. For the industrial gear surface, it has been shown that texture varies along the tooth and, therefore, causes a dependency of the roughness parameters on the location of the evaluation region (see Section 3).…”
Section: Calibration Of the Pmsmentioning
confidence: 99%
“…The contributions due to the instrument and its environment are small compared to the characteristics of the object. Previous investigations have already shown how the sensitivity of roughness parameters to the heterogeneity of textures can be determined [27]. For the industrial gear surface, it has been shown that texture varies along the tooth and, therefore, causes a dependency of the roughness parameters on the location of the evaluation region (see Section 3).…”
Section: Calibration Of the Pmsmentioning
confidence: 99%
“…These influence quantities are only given to show how they affect the metrological characteristics-it is not expected that they would be used to estimate uncertainty. Estimating measurement uncertainty for a surface topography measurement (and a texture parameter calculation using the measured data) is highly complex (see examples in Haitjema [36][37][38][39][40]) and the metrological characteristics have been explicitly defined so as to make this process simpler to apply in industry. A number of example uncertainty budgets using metrological characteristics have been published [4,36,[41][42][43][44] but the publication of more examples is required to build up the database and promote industrial adoption.…”
Section: Metrological Characteristic: Characteristic Of Measuring Eq...mentioning
confidence: 99%
“…For the input variables defined above, it is established that variability due to the process of obtaining the sampled coordinates responds to a normal distribution with a mean of the raw coordinate value and a standard deviation equal to 2% of the sampling step [ 28 , 29 ]. In order to analyze the variability of the z-coordinates, it was necessary to perform a repeatability study of the measurements [ 30 ]. That is to say, measuring the same profile a large number of times, by the same operator, with the same measurement procedure, same measuring system, and same operation conditions [ 31 ].…”
Section: Evaluation Procedures Of Roughness Parametersmentioning
confidence: 99%
“…In order to analyze the variability of the z-coordinates, it was necessary to perform a repeatability study of the measurements [ 30 ]. That is to say, measuring the same profile a large number of times, by the same operator, with the same measurement procedure, same measuring system, and same operation conditions [ 31 ].…”
Section: Evaluation Procedures Of Roughness Parametersmentioning
confidence: 99%